Vertical spin valve performance of NiFe/Co-PANI/NiFe system - Nemade Kailash; Maheshwary Prashant (St. Petersburg Polytechnical University Journal: Physics and Mathematics)
The organic materials are found to be potent candidates for spintronics applications. Here, we have presented a cobalt-loaded polyaniline (Co-PANI)-based spin valve with NiFe alloy as ferromagnetic contacts. The spin valve signal was observed at temperatures from 10 K to 300 K. The IV curve of the spin valve exhibited a linear relationship, which showed that Co-PANI behaved like metal in this valve. The highest value of the magnetoresistance (MR) was found to be 8.13% at 10 K, whereas it decreased to 3.32 % at 300 K. Similarly, the bias current effect showed that the highest value of MR was 3.46 % for 10 A, which reduced down to 0.93% for 40 A.